Significance of marital love in the canonical and pastoral aspect - Czaja, Arkadiusz Mirosław (Prawo Kanoniczne, 2018)
Love is an important integrating factor of the marital-family life. It is not a legal entity; however, it plays a very important role in the life of man. Without love spouses are deprived of stimuli which contribute greatly and enable to achieve goals set for the marriage. When there is no love between fiancées, one of them might become alienated, they may also be unwilling to get married as result, which in turn would lead to declaring their marriage invalid in both cases. Marital love is crucial to ensure the expression of marital harmony between husband and wife properly and to perform conjugal and parental duties in a responsible way. The Roman Catholic Church, from the beginning of its apostolic activity, has protected the value of marriage and family with constant prayer, special concern and the blessing. Marital love has a primary importance in the entire community of life of a married couple. It is essential for their mutual and full development. Love is an important integrating factor of the marital life. Marital love facilitates the execution of tasks that spouses and then parents have to do. Excluding the above-mentioned goals set for the marriage as well as defects in the agreement between the spouses result in the fact the marriage is invalid. Responsible marriage is inseparable of love, which should be the basis for the conjugal life of the couple. There is no denying that love of the spouses, whose desire is to live together, contributes greatly to the marital harmony between husband and wife and stimulates mutual devotion and acceptance of the couple.